Expo-event "YAAY DUND - Regenerating the living world - Belmin, Raphael; Thouvenot, Marie (2024)
The Dynamique pour une transition Agroécologique au Sénégal (DyTAES), on the initiative of the Centre de coopération en Recherches Agronomiques pour le Développement (CIRAD), organized an exhibition-event entitled "YAAY DUND - Regenerating the living world", as part of the Dakar 2024 Biennale of Contemporary African Art, from November 13 to December 08, 2024. The exhibition highlighted the fundamental but all too often overlooked role of women in food systems and the agroecological transition in Africa. The exhibition-event was held in an eco-designed ephemeral building at the foot of the African Renaissance monument in Dakar, Senegal. For the duration of the exhibition, the site hosted a rich program of events combining arts, science and political dialogue in order to highlight targeted themes related to agroecology and gender (conferences, round tables, artistic performances). The YAAY DUND exhibition served as a symbolic venue to celebrate the 5th anniversary of DyTAES, as well as the joint anniversaries of CIRAD, the Institut Sénégalais de Recherches Agricoles (ISRA) and the Institut de Recherche pour le Développement (IRD).